Microwave-Assisted Organic Reactions: Eco-friendly Synthesis of Dibenzylidenecyclohexanone Derivatives via Crossed Aldol Condensation - Sri Handayani; Cornelia Budimarwanti; Winarto Haryadi (Indonesian Journal of Chemistry, 2017)
The synthesis of dibenzylidenecyclohexanone derivatives via environmentally friendly Microwave Assisted Organic Synthesis (MAOS) crossed aldol condensation had been carried out. The condensation reaction to synthesize the dibenzylidenecyclohexanone 8b was performed by reacting benzaldehyde 4 and cyclohexanone 2 (mole ratio of 2:1) with NaOH as catalyst for 2 min under microwave irradiation. The benzaldehyde derivatives used in this study were 4-methoxybenzaldehyde and 3,4-dimethoxybenzaldehyde and gave of (2E,6E)-bis(4-methoxy benzylidene)cyclohexanone 8a and (2E,6E)-bis(3,4-dimethoxybenzylidene)cyclohexanone 8c, respectively. The study was commenced by searching the optimum concentration of NaOH. The reaction yield was determined by TLC scanner and the structure was elucidated by FTIR and NMR spectrometers. For the comparison, the reaction was also carried out by using stirring method. The results showed that optimum concentration of NaOH was 5 mmole. By using the optimum condition via MAOS method, the compounds 8a, 8b and 8c were obtained in 100, 98 and 93%, respectively. The research also proved that the method of dibenzylidenecyclohexanones (8) synthesis using MAOS was more efficient than stirring method.